Tìm x để 2x – 3) – 5 = 2 – (2x + 1). Kết quả là x =

Question

Tìm x để 2x – 3) – 5 = 2 – (2x + 1). Kết quả là x =

in progress 0
Ladonna 4 years 2020-11-09T13:03:11+00:00 2 Answers 80 views 0

Answers ( )

    0
    2020-11-09T13:04:45+00:00

    Đáp án:

     

    Giải thích các bước giải:

     `( 2x – 3) – 5 = 2 – (2x + 1)`

    `⇔ 2x-3-5=2-2x-1`

    `⇔ 4x=9`

    `⇔ x=3/2`

    Vậy `S=3/2`

    0
    2020-11-09T13:05:10+00:00

    Đáp án:

      2x-3-5=2-2x-1

    <=>4x=9

    <=>x=4/9

    Giải thích các bước giải:

     

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )